1987
DOI: 10.1002/ajmg.1320270415
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkly skin syndrome: Phenotype and additional manifestations

Abstract: The wrinkly skin syndrome is an autosomal recessive disorder characterized by wrinkling of the skin of the dorsum of the hands and feet, decreased elastic recoil of the skin, an increased number of palmar and plantar creases, multiple musculoskeletal abnormalities, microcephaly, and mental retardation. Our patient is characteristic of the syndrome as previously described, and confirms the presence of mental retardation and microcephaly as component manifestations, with the additional findings of connective tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
2
16
2
Order By: Relevance
“…The WSS patients had clinical features similar to those described in previous reports [Gazit et al, 1973;Karrar et al, 1983;Casamassima et al, 1987;Hurvitz et al, 1990;Morava et al, 2005] and their phenotype resembled closely the one described for autosomal recessive CLGDD/ARCL type II [Agha et al, 1978;Philip, 1978;Ogur et al, 1990;Kreuz and Wittwer, 1993;Imaizumi et al, 1994;Loeys et al, 2002]. Ogur et al [1990] reported Turkish sibs where the boy was severely affected with the classical form of CLGDD, while his sister showed improvement with age and at the age of 6.5 years presented with a relatively mild disease, including cutaneous manifestations similar to those found in WSS.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The WSS patients had clinical features similar to those described in previous reports [Gazit et al, 1973;Karrar et al, 1983;Casamassima et al, 1987;Hurvitz et al, 1990;Morava et al, 2005] and their phenotype resembled closely the one described for autosomal recessive CLGDD/ARCL type II [Agha et al, 1978;Philip, 1978;Ogur et al, 1990;Kreuz and Wittwer, 1993;Imaizumi et al, 1994;Loeys et al, 2002]. Ogur et al [1990] reported Turkish sibs where the boy was severely affected with the classical form of CLGDD, while his sister showed improvement with age and at the age of 6.5 years presented with a relatively mild disease, including cutaneous manifestations similar to those found in WSS.…”
Section: Discussionsupporting
confidence: 71%
“…We did not observe dwarfism, oligophrenia or corneal degeneration as described for De Barsy syndrome (OMIM 219150) [de Barsy et al, 1968]. Although both, GO and WSS, are characterized by excessive wrinkling of the skin, the degree and the extent of the wrinkling is different, as previously pointed out by Hunter et al, [1978] and Casamassima et al, [1987]. In our study, babies and young children with GO had ''droopy skin,'' particularly at the cheeks, but the wrinkling was confined to the dorsum of hands and feet and became apparent over the abdomen only in a sitting position.…”
Section: Discussionsupporting
confidence: 55%
“…Dermatoglyphic studies of these three conditions showed no significant abnormality other than an increased number of palmar and plantar creases, especially in reports of WSS (Gazit et al, 1973;Casamassima et al, 1987;Hurvitz et al, 1990). Many patients exhibit single transverse palmar creases.…”
Section: Dermatologic Aspectsmentioning
confidence: 90%
“…The skin heals normally and there is no tendency to easy bruising or bleeding (Casamassima et al, 1987).…”
Section: Dermatologic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation